The Influence of Work Environment, Leadership Style and Workload on Employee Job Satisfaction - Saripudin, Asep; Perkasa, Didin Hikmah (Lentera Ilmu Nusantara, 2024)
The importance of the current role of Human Resource Management in an organization or agency as one of the factors in driving the progress of an organization or agency. To increase the effectiveness and optimize an activity, one of the most important resources a company or agency has is good quality human resources. The research design uses a quantitative descriptive approach. The data in this study were obtained from 45 respondents who were the Liaison Agency Officers of the Province of Lampung in Jakarta by using a questionnaire as a data collection tool using the survey method. Data analysis in this study used the SEM PLS test tool to test discriminate validity, convergent validity, composite reliability, outer model, inner model and hypothesis testing. The first stage in this study was to test the validity of the questions for each variable along with its reliability. The second stage examines the effect of each variable. The results of the study show that there is an effect of the work environment on employee job satisfaction, leadership style has no effect on employee job satisfaction and the influence of workload on employee job satisfaction